Clearance of bile and trypsin in rat lungs following aspiration of human gastric fluid. (2nd January 2016) - Leung, Jason H.; Chang, Jui-Chih; Foltz, Emily; Bell, Sadé M.; Pi, Cinthia; Azad, Sassan; Everett, Mary Lou; Holzknecht, Zoie E.; Sanders, Nathan L.; Parker, William; Davis, R. Duane; Keshavjee, Shaf; et al.
ABSTRACT: Purpose: In the clinical setting, there is no reliable tool for diagnosing gastric aspiration. A potential way of diagnosing gastric fluid aspiration entails bronchoalveolar lavage (BAL) with subsequent examination of the BAL fluid for gastric fluid components that are exogenous to the lungs. The objective of this study was to determine the longevity of the gastric fluid components bile and trypsin in the lung, in order to provide an estimate of the time frame in which assessment of these components in the BAL might effectively be used as a measure of aspiration.Materials and Methods: Human gastric fluid (0.5 mg/kg) was infused in the right lung of intubated male Fischer 344 rats ( n = 30). Animals were sacrificed at specified times following the experimentally induced aspiration, and bronchoalveolar lavage fluid (BALF) was collected. Bile concentrations were analyzed by an enzyme-linked chromatogenic method, and the concentration of trypsin was quantified using an ELISA. Data were analyzed using non-linear regression and a one-phase decay equation.Results: In this experimental model, the half-life of bile was 9.3 hours ( r 2 = 0.81), and the half-life of trypsin was 9.0 hours ( r 2 = 0.68).Conclusions: The half-lives of bile and trypsin in the rodent aspiration model suggest that the ability to detect aspiration may be limited to a few days post-aspiration. If studies using rats are any indication, it may be most effective to collect BAL samples within the first 24 hours of suspected aspiration events in order to detect aspiration.